TLR4+CXCR4+ plasma cells drive nephritis development in systemic lupus erythematosus. Issue 10 (20th June 2018) - Ma, Kongyang; Li, Jingyi; Wang, Xiaohui; Lin, Xiang; Du, Wenhan; Yang, Xi; Mou, Fangxiang; Fang, Yongfei; Zhao, Yanbin; Hong, Xiaoping; Chan, Kwok Wah; Zhang, Xiaoming; et al.
Abstract : Objectives: In patients with systemic lupus erythematosus (SLE), immune tolerance breakdown leads to autoantibody production and immune-complex glomerulonephritis. This study aimed to identify pathogenic plasma cells (PC) in the development of lupus nephritis. Methods: PC subsets in peripheral blood and renal tissue of patients with SLE and lupus mice were examined by flow cytometry and confocal microscopy, respectively. Sorting-purified PCs from lupus mice were adoptively transferred into Rag2 -deficient recipients, in which immune-complex deposition and renal pathology were investigated. In culture, PCs from lupus mice and patients with SLE were treated with a TLR4 inhibitor and examined for autoantibody secretion by enzyme-linked immunospot assay (ELISPOT). Moreover, lupus mice were treated with a TLR4 inhibitor, followed by the assessment of serum autoantibody levels and glomerulonephritis activity. Results: The frequencies of TLR4 + CXCR4 + PCs in peripheral blood and renal tissue were found significantly increased with the potent production of anti-dsDNA IgG, which were associated with severe renal damages in patients with SLE and mice with experimental lupus. Adoptive transfer of TLR4 + CXCR4 + PCs from lupus mice led to autoantibody production and glomerulonephritis development in Rag2 -deficient recipients. In culture, TLR4 + CXCR4 + PCs from both lupus mice and patients with SLE showed markedly reduced anti-dsDNA IgG secretion on TLR4 blockade. Moreover, in vivo treatment with TLR4 inhibitor significantly attenuated autoantibody production and renal damages in lupus mice. Conclusions: These findings demonstrate a pathogenic role of TLR4 + CXCR4 + PCs in the development of lupus nephritis and may provide new therapeutic strategies for the treatment of SLE.